2016
DOI: 10.1038/srep27916
|View full text |Cite
|
Sign up to set email alerts
|

The Hydration Structure at Yttria-Stabilized Cubic Zirconia (110)-Water Interface with Sub-Ångström Resolution

Abstract: The interfacial hydration structure of yttria-stabilized cubic zirconia (110) surface in contact with water was determined with ~0.5 Å resolution by high-resolution X-ray reflectivity measurement. The terminal layer shows a reduced electron density compared to the following substrate lattice layers, which indicates there are additional defects generated by metal depletion as well as intrinsic oxygen vacancies, both of which are apparently filled by water species. Above this top surface layer, two additional ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 44 publications
(72 reference statements)
3
33
0
1
Order By: Relevance
“…The hydration structure at yttria stabilized zirconia and water interface in hydrothermal condition with sub angstrom resolution confirmed that Y 3+ and ZrO nanoparticles could release from the bulk because of chemisorbed water to the Zr sites of the zirconia surface and the OH − groups initiate the stressed sites and precede the degradation of the substrate. Due to the degradation phenomenon, the metal ions could be provided from the surface to combine with zinc and phosphate to form zinc phosphate coating 28) , which is similar to the previously confirmed zinc phosphatizing mechanisms.…”
Section: Coating Layer Fabricationsupporting
confidence: 82%
“…The hydration structure at yttria stabilized zirconia and water interface in hydrothermal condition with sub angstrom resolution confirmed that Y 3+ and ZrO nanoparticles could release from the bulk because of chemisorbed water to the Zr sites of the zirconia surface and the OH − groups initiate the stressed sites and precede the degradation of the substrate. Due to the degradation phenomenon, the metal ions could be provided from the surface to combine with zinc and phosphate to form zinc phosphate coating 28) , which is similar to the previously confirmed zinc phosphatizing mechanisms.…”
Section: Coating Layer Fabricationsupporting
confidence: 82%
“…Multiple water layers have not, to our knowledge, been studied computationally on actinide or lanthanide oxides, although there is some very recent work on yttriastabilised zirconia, 27,28 a system which is isostructural with the lanthanide and actinide oxides. This paucity is in stark contrast to water adsorption on other metal oxides such as Cassiterite (SnO2) and rutile (TiO2), which has been studied extensively.…”
Section: Resultsmentioning
confidence: 99%
“…11 This behavior can be attributed mainly to the reduced amount of oxygen vacancies on TiO 2 surfaces compared to YSZ, which act as active sites for water adsorption. 69,70,74 Furthermore, DFT calculations suggest that on amorphous TiO 2 the adsorption of hydroxyl groups is even less favorable compared to anatase TiO 2 , 75 which is also supported by the lower protonic conductivity in the case of the amorphous coating, especially at higher temperatures. However, water condensation in the pores may also play a role in the higher protonic conductivity in the case of the YSZ thin film with the crystalline TiO 2 (note that the pore size is also reduced due to the coating).…”
Section: (B) and (C)mentioning
confidence: 99%
“…However, also surface defects, such as oxygen vacancies, play a significant role in the formation of surface protons as water fills the oxygen vacancies and forms hydroxyl groups. [68][69][70] In Kroeger-Vink notation, their formation is given by the reaction: 15,35,71,72…”
Section: Humid Atmospherementioning
confidence: 99%